Sex-allocation trade-offs and their genetic architecture revealed by experimental evolution - Jörn F. Gerchen; Nora Villamil-Buenrostro; Xinji Li; Ehouarn Le Faou; John R. Pannell (Proceedings of the National Academy of Sciences, 2026)
The theory of sex allocation is hailed as one of evolutionary biology’s great successes. But while it has successfully predicted strategies of resource allocation to male versus female offspring under a wide range of conditions in species with separate sexes, it has been difficult to verify the fundamental assumption of a direct genetic trade-off between male and female allocations when both sexes are expressed together in the same individuals. This trade-off assumption supposes that mutations that increase an individual’s male allocation reduce its female allocation, and vice versa. Here, we use experimental evolution to generate wide variation in sex allocation in a wind-pollinated annual plant. We demonstrate a clear trade-off between the two sexual functions over time, with populations repeatedly evolving increased male and correspondingly reduced female allocation. Quantitative trait locus (QTL) analysis performed on multiple crosses further reveals the segregation of allelic variation at “trade-off loci.” Taken together, our results demonstrate a genetic trade-off in sex allocation in hermaphrodites and provide compelling evidence for sex-allocation trade-off loci. Our study thus verifies the fundamental assumption of sex-allocation theory and secures its general applicability to both dioecious and hermaphroditic species.